Biochar field testing in the UK: outcomes and implications for use. Issue 2 (April 2013) - Hammond, Jim; Shackley, Simon; Prendergast-Miller, Miranda; Cook, Jason; Buckingham, Sarah; Pappa, Valentini A
Background: There is a lack of biochar field trials in temperate climate regions. Wood biochar was applied during 2009–2011 to seven field experiments on five working farms in the UK, for arable, legume, horticultural and root crops.Results: Three trials showed no significant (p > 0.05) effect on crop yield, two showed positive effects of 5–6%, one showed a very strong increase of 100% and one showed a decrease of 2–16%. A meta-analysis of effect sizes was conducted for all treatments (n = 47), which showed a significant (p < 0.05) positive effect, increasing average yield by 0.4 t ha -1 . Biochar application rates of 20 t ha -1 or under led to the greater benefits.Conclusion: This paper shows that, in some situations, biochar can bring benefits in modern temperate farming.